Application of Nanotechnology in Chemical Enhanced Oil Recovery and Carbon Storage - Al-Anssari, Sarmad Foad Jaber (Curtin University, 2018)
Nanofluids gaining increased importance in science and industry including enhanced oil recovery. In this work, the ability of nanoparticles to alter the wettability of oil-wet surfaces towards water-wet at reservoir conditions and the synergistic effect of nanoparticle-surfactant combinations on nanofluid interfacial properties and nanofluid stability were systematically examined using several nano-silica dispersions. This study not only presents novel nanofluid formulations for wettability alteration but also introduced the first insight into nanoparticle-surfactant interactions in saline environments.